Plato, passions and criticism of the populism - Vallejo Campos, Álvaro Pablo (ΠΗΓΗ/FONS, 2020)
The main thesis of this paper is that the political transcendence of passions determines Plato’s ethical and political points of view. The first time that he deals systematically with passions, as occurs in the Gorgias, they are directly implicated in the critic of imperialism and the rhetorical procedures of Athenian democracy. They are also an essential part of politics conceived as an art. In the Republic , the ideal city emerges as the necessity of practicing a purge of passions in the luxuriant or feverish city that has to be purged. The importance of this issue derives from the fact that the theory of justice in the individual and the city consists of a normative ideal on the relations that have to be established between passions and reason. As a consequence, the sequence of the degenerated forms of the ideal state can be interpreted as an increasing model of the illegitimate irruption of passions in the ill society opposed to it.
Keywords: Plato; passions; politics; rhetoric; ideal state; justice; populism